Leveraging Science to Advance Health Equity: A Regional Health Policy Research Center’s Approach - Holden, Kisha B. (Ethn Dis, 2019)
Advancing health equity and reducing disparities through evidence-based policy research requires the expertise, insights, and active participation of various policy stakeholders – particularly those representing vulnerable populations who may be disproportionately affected by such policies. Unfortunately, there are few sustainable settings for these diverse stakeholders to convene, share their knowledge, develop and execute research in a collaborative fashion, and effectively translate evidence-based findings. The development of a health policy-focused center supports the collaborative structure needed to present a unified, multi-disciplinary approach toward informing health policy. The Transdisciplinary Collaborative Center for Health Disparities Research (TCC) at Morehouse School of Medicine (U54MD008173) was funded in 2012 by the National Institute on Minority Health and Health Disparities (NIMHD) as an innovative approach for conducting health policy research and disseminating evidence-based science to diverse stakeholders. This article provides an overview of the research projects, pilot project programs, infrastructure cores, communications, and strategic dissemination activities supported by the TCC.